Arab France Islam and the making of modern Europe, 1798-1831 - Coller, Ian (University of California Press, 2011)
Many think of Muslims in Europe as a 20th century phenomenon, but this book brings to life a lost community of Arabs who lived through war, revolution, and empire in early 19th century France.